Protein-based double-network hydrogels mimicking oral mucosa - Yu Zhang; Yu Zhang; Liang Dong; Keqing Wang; Yuanqi Cheng; Tian Gao; Jiapeng Yang; Xiaochen Shen; Yi Cao; Bin Xue (Frontiers in Chemistry)
The oral mucosa plays a critical role in protecting the body from external threats and serves as a key site for drug absorption. However, ethical concerns and the high costs associated with animal models traditionally used for oral mucosa research have increased the demand for reliable alternatives. In this study, we developed two types of protein-based double-network hydrogels to replicate the mechanical and structural properties of buccal mucosa and hard palate, respectively. By incorporating polyprotein into the rigid network and elastin-like peptides as the loose network, we fabricated hydrogels that closely resemble the physical properties of natural oral mucosa. These hydrogels exhibit a microporous structure, as well as surface and mechanical properties, and particle permeability comparable to native tissue, while maintaining excellent biocompatibility. We anticipate that these hydrogels can serve as model systems for investigating drug delivery, pathogen interactions, and aerosol particle adsorption in the oral mucosa. The design principles presented in this study could also be extended to fabricate protein-based biomaterials that mimic mucosal tissues in the respiratory, gastrointestinal, and urogenital tracts, providing a general approach for developing biomimetic materials for mucosal tissues.